Anti-wood-fungal performance of methanol extracts of Rhizophora apiculata and R. mucronata barks - Ismail, Jusoh; Zaini, Assim; Nur Syuhadah, Salim (BioResources, 2020)
Various plant parts of Rhizophora species have been used in the treatment of a variety of diseases and illnesses. However, they have not been tested for antifungal properties related to wood decay fungi, especially the bark extractives. This study examined the methanol (MeOH) crude extracts of R. apiculata and R. mucronata barks in terms of the amount of extracts obtained and their antifungal properties. The antifungal activities of the crude MeOH extracts of both species were determined using the agar dilution method. Methanol crude extract from R. apiculata and R. mucronata were 10.8% and 15.7%, respectively and were toxic to Chaetomium globosum and Gloeophyllum trabeum at the concentration of 50 mg/mL.